Homemade Pressure Washer System (DIY) - Kamaruddin, Syamsul Azrin; Taranjit Singh,; Syafiq Ikhwan,; Sathesh Kumaar, (Multidisciplinary Applied Research and Innovation, 2023)
The pressure washer system is a mechanical device that is used to remove dirt and unwanted things from surfaces and object[1]. However, there are few problems when it comes to cleaning process, firstly the effectiveness of an existing water supply to produce a water jet to clean dirty surface most of underground pipe source flows at existing water pressure at 25 kPa. The cost of pressure washer system differs according to its specification and design [2]. The better the quality of the product, higher the cost price. Hence high cost cannot be afforded by B40 society to use for effective cleaning process [3]. Hence the main objective of this project is to increase the pressure of existing water supply without using any pump or electricity and at same time it is environmentally friendly. Not only that, this homemade pressure washer system aims to introduce a cost-saving method for B40 society. This project consisting of simple fabrication process whereby only PVC pipe and fittings, valve, nozzle and storage bottle is utilized to construct the final product. It is easy to assemble and requires minimum machining process. As a result, the project is able to increase the existing water supply by 52% which is able to generate 200 kPa of output water pressure. Not only that, this project able to generate a maximum output velocity of water at 20.37 m/s compared to existing water supply that is measured at 0.61 m/s. Apart from this project has achieved its another objective which is low-cost production whereby total cost is RM 47.15 in which is lesser than maximum targeted price at RM 60.00.